EFEITOS DA SUPLEMENTAÇÃO COM NOVA TECNOLOGIA PARA OBTENÇÃO DO COLÁGENO HIDROLISADO DE BAIXO PESO MOLECULAR NAS MARCAS DE EXPRESSÃO E NA QUALIDADE DA PELE NA REGIÃO ORBICULAR DO OLHO EM MULHERES DE MEIA IDADE (CIPEEX, 2026)
Introduction: The skin is the largest organ in the human body and performs functions of protection, regulation, and cellular communication. Aging and environmental factors promote visible structural changes, such as wrinkles and dryness. Nutrition plays a relevant role in health, and supplementation with collagen peptides has been associated with improved elasticity, hydration, and wrinkle reduction, although more evidence is needed. Objective: To evaluate the effects of oral supplementation with Verisol® hydrolyzed collagen (2.5 g/day) on expression lines and skin quality in the orbicularis oculi region of middle-aged women. Method: Fifty women aged 35 to 58, sedentary for at least one year, were recruited. Consumers, users of protein supplements, restorative cosmetics, or those undergoing cosmetic procedures were excluded. Volunteers received 2.5 g/day of Verisol® collagen for three months. Weight, height, BMI, body composition, dietary intake, and characteristics (hydration, oiliness, and specifications) were assessed using specific equipment. Statistical analysis used GraphPad Prism 5.0, with paired and unpaired Student's t-test (p
Keywords: skin; collagen; supplementation; wrinkles